Fiscal Control Instrument For Quantifying Tax Evasion - Nitu, Alin Sergiu; Constantin, Aurelian; Constantin, Marcel (Acta Universitatis Danubius. Œconomica, 2022)
The current conditions in our country, when the budget revenues become more and more insufficient to support public spending, strictly require the analysis and cessation of tax evasion, as a brake on achieving budget balance. Through its forms, expressed by the phrase legal/illegal, tax evasion is a daily reality, a component of the underground economy present throughout the world, connected with globalization regardless of the level of development of areas and states where it manifests itself. It is already known that tax evasion is an economic scourge linked to and dependent on the system of permissive taxation and regulation of economic activities, which has made, makes and will be the subject of all authorities involved in sizing, accounting and reducing/eliminating it. As tax control is an instrument of coercion to attract tax revenues, to find deviations from the normal tax collection, its results can generate a method of sizing the effects of tax evasion, implicitly estimating it at various levels of research including level national and/or international. Fiscal control, like accounting, is based on accounting information, which provides the first clues about the operation it describes, linking its potential to be hidden and indicating a certain value of it. As a method of estimating tax evasion, the use of tax control can be described briefly, in stages, as follows: -analysis of the public database; - identifying the possible source of extracting the accounting information, which in our opinion is the ANAF website, this being the state body that collects, supervises, and controls the public revenues; - extracting the documentary material that provides pertinent information regarding fiscal control, the most indicated being the annual performance report; - centralization of the necessary information (no. controls, the value of taxes and stolen taxes, analytical and synthetic); - designing a model of data connection, quantification, estimation, and extrapolation at the analytical and synthetic level. The results of this method, if possible, can be correlated with other information by making certain adjustments which ultimately give the possibility of their normal credibility.